2017
DOI: 10.1002/jppr.1264
|View full text |Cite
|
Sign up to set email alerts
|

Hospital pharmacists' beliefs about optimising statin therapy in older inpatients

Abstract: This study explored hospital pharmacists' perspectives about optimising statin therapy in older inpatients in Australia. An anonymous questionnaire using standardised questions in the form of five-point Likert scales to capture pharmacists' attitudes toward their role in statin optimisation, compliance of statin therapy with existing guidelines, knowledge of statin-related side effects and clinical recommendations such as starting and ceasing or deprescribing therapy, was administered. A total of 108 hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…Questionnaires using regular knowledge and attitude questions are of course still of interest in their own right and it is of interest to see how the issue of deprescribing is becoming high on the agenda of pharmacists in one such ‘regular’ questionnaire study. The study reported by Wu et al . shows that the surveyed pharmacists are ready to take on a role of managing statin therapy in elderly patients and feel there is room for deprescribing of these drugs for some patients.…”
mentioning
confidence: 99%
“…Questionnaires using regular knowledge and attitude questions are of course still of interest in their own right and it is of interest to see how the issue of deprescribing is becoming high on the agenda of pharmacists in one such ‘regular’ questionnaire study. The study reported by Wu et al . shows that the surveyed pharmacists are ready to take on a role of managing statin therapy in elderly patients and feel there is room for deprescribing of these drugs for some patients.…”
mentioning
confidence: 99%